(untitled) (Revista Diálogos, 2017)
Na abordagem bakhtiniana, o conceito de vozes sociais está relacionado a diferentes posicionamentos, pontos de vista, posturas ideológicas. Neste trabalho, objetivamos fazer uma reflexão teórica acerca do desenvolvimento dessa categoria nos escritos do chamado Círculo de Bakhtin. Atrelado a este debate, apresentamos, também, uma discussão sobre as categorias discurso citado e acentos apreciativos, recursos linguístico-discursivos que marcam, na materialidade textual, posicionamentos avaliativos na luta pela produção dos sentidos e manifestam o confronto entre diferentes vozes sociais. In the Bakhtinian approach, the concept of social voices is related to different positions, points of view, ideological postures. In this work, we aim to engage in a discussion about the development of this category in the writings of the so-called Circle of Bakhtin. From the debate about social voices, we work the concept of heteroglossia, understood as the multiplicity and the heterogeneity of social voices that are interrelated in the universe of dialogical relationships. In this perspective, we also present, in this article, a discussion about the categories reported speech and appreciative accents, linguistic and discursive resources that mark evaluative positions in the fight of the production of meaning and express the confrontation between different social voices.